Revision of the Afrotropical species of Gonatopus group 3 (Hymenoptera: Dryinidae), with description of a new species from Ghana - Guglielmino, Adalgisa; Olmi, Massimo (Zootaxa, 2014)
The Afrotropical species of Gonatopus Ljungh, 1810 group 3 are revised. A new species is described from Ghana, Eastern Region: G. schwarzorum Guglielmino & Olmi, sp. nov. A new key to the females of the Afrotropical species of Gonatopus group 3 is presented.